The impaired distribution of adenosine deaminase isoenzymes in multiple sclerosis plasma and cerebrospinal fluid - Kutryb-Zajac, Barbara; Kawecka, Ada; Caratis, Fionä; Urbanowicz, Krzysztof; Braczko, Alicja; Furihata, Tomomi; Karaszewski, Bartosz; Smolenski, Ryszard T.; Rutkowska, Aleksandra (Frontiers in Molecular Neuroscience, 2022)
Background Adenosine deaminase (ADA) via two isoenzymes, ADA1 and ADA2, regulates intra- and extracellular adenosine concentrations by converting it to inosine. In the central nervous system (CNS), adenosine modulates the processes of neuroinflammation and demyelination that together play a critical role in the pathophysiology of multiple sclerosis (MS). Except for their catalytic activities, ADA isoenzymes display extra-enzymatic properties acting as an adhesion molecule or a growth factor. Aims This study aimed to explore the distribution and activity of ADA1 and ADA2 in the plasma and the CSF of MS patients as well as in the human brain microvascular endothelial cells (HBMEC), human brain vascular pericytes and human astrocytes. Methods and results The enzyme assay following reverse phase-high performance liquid chromatography (HPLC) analysis was used to detect the ADA1 and ADA2 activities and revealed an increased ratio of ADA1 to ADA2 in both the plasma and the CSF of MS patients. Plasma ADA1 activity was significantly induced in MS, while ADA2 was decreased in the CSF, but significance was not reached. The brain astrocytes, pericytes and endothelial cells revealed on their surface the activity of ADA1, with its basal level being five times higher in the endothelial cells than in the astrocytes or the pericytes. In turn, ADA2 activity was only observed in pericytes and endothelial cells. Stimulation of the cells with pro-inflammatory cytokines TNFα/IL17 for 18 h decreased intracellular nucleotide levels measured by HPLC only in pericytes. The treatment with TNFα/IL17 did not modulate cell-surface ATP and AMP hydrolysis nor adenosine deamination in pericytes or astrocytes. Whereas in endothelial cells it downregulated AMP hydrolysis and ADA2 activity and upregulated the ADA1, which reflects the ADA isoenzyme pattern observed here in the CSF of MS patients. Conclusion In this study, we determined the impaired distribution of both ADA isoenzymes in the plasma and the CSF of patients with MS. The increased ADA1 to ADA2 ratio in the CSF and plasma may translate to unfavorable phenotype that triggers ADA1-mediated pro-inflammatory mechanisms and decreases ADA2-dependent neuroprotective and growth-promoting effects in MS.